Associations between MRI‐assessed locus coeruleus integrity and restriction spectrum imaging of cortical gray matter microstructure. (December 2021) - Elman, Jeremy A.; Puckett, Olivia K.; Hagler, Donald J.; Pearce, Rahul C.; Fennema‐Notestine, Christine; Hatton, Sean N.; Dale, Anders M.; Panizzon, Matthew S.; Lyons, Michael J.; Franz, Carol E.; Kremen, William S.
Abstract: Background: The locus coeruleus (LC) serves as the primary source of norepinephrine for the brain. Findings that the LC is one of the earliest sites of tau pathology make it a key structure in the early stages of Alzheimer's disease (AD) progression. An important question is whether measures of LC integrity are associated with indexes of brain structure that may suggest broader patterns of neurodegeneration, particularly if such patterns are detectable prior to substantial macrostructural change. We therefore examined whether LC structural integrity was associated with differences in cortical gray matter microstructure among adults in early old age. Method: Participants were 435 men (mean age=67.5; range=62‐71.7) from the Vietnam Era Twin Study of Aging (VETSA). Rostral LC structural integrity was indexed by contrast‐to‐noise ratio (LCCNR ) from a neuromelanin‐sensitive MRI scan. Restriction spectrum imaging (RSI), an advanced multi‐shell diffusion technique, was used to characterize cortical microstructure, modeling diffusion in restricted, hindered, and free water compartments. Associations between LCCNR and isotropic diffusion within each compartment were examined for bilateral averages of 34 cortical ROIs defined by the Desikan‐Killiany parcellation. As a sensitivity analysis, we also examined whether LCCNR was associated with mean diffusivity (MD), a conventional diffusion tensor imaging (DTI) metric, or cortical thickness in the same regions. Result: After correction for multiple comparisons, higher LCCNR (greater structural integrity) was significantly associated with higher hindered isotropic diffusion and lower free water diffusion across multiple brain regions. In contrast, LCCNR was only associated with lower MD in one brain region and there were no associations with cortical thickness after correction. Conclusion: These results provide evidence that lower MRI‐assessed LC integrity is associated with patterns of cortical microstructure that may reflect a reduction in cellular membranes due to broader neurodegenerative processes. Individual differences in LC integrity were only detected with more advanced measures of microstructure that may be more sensitive to early changes than conventional diffusion imaging or macrostructural measures. These results highlight the potential utility for MRI of the LC and cortical microstructure in early identification of AD risk.